set A = [.0,1.];

deffunc H_{1}( Element of [.0,1.], Element of [.0,1.]) -> Element of [.0,1.] = In ((($1 * $2) / (($1 + $2) - ($1 * $2))),[.0,1.]);

ex f being Function of [:[.0,1.],[.0,1.]:],[.0,1.] st

for x, y being Element of [.0,1.] holds f . (x,y) = H_{1}(x,y)
from BINOP_1:sch 4();

then consider f being BinOp of [.0,1.] such that

A1: for x, y being Element of [.0,1.] holds f . (x,y) = H_{1}(x,y)
;

reconsider ff = f as BinOp of [.0,1.] ;

take ff ; :: thesis: for a, b being Element of [.0,1.] holds ff . (a,b) = (a * b) / ((a + b) - (a * b))

let a, b be Element of [.0,1.]; :: thesis: ff . (a,b) = (a * b) / ((a + b) - (a * b))

reconsider aa = a, bb = b as Element of [.0,1.] ;

ff . (a,b) = H_{1}(aa,bb)
by A1;

hence ff . (a,b) = (a * b) / ((a + b) - (a * b)) by SUBSET_1:def 8, HamIn01; :: thesis: verum

deffunc H

ex f being Function of [:[.0,1.],[.0,1.]:],[.0,1.] st

for x, y being Element of [.0,1.] holds f . (x,y) = H

then consider f being BinOp of [.0,1.] such that

A1: for x, y being Element of [.0,1.] holds f . (x,y) = H

reconsider ff = f as BinOp of [.0,1.] ;

take ff ; :: thesis: for a, b being Element of [.0,1.] holds ff . (a,b) = (a * b) / ((a + b) - (a * b))

let a, b be Element of [.0,1.]; :: thesis: ff . (a,b) = (a * b) / ((a + b) - (a * b))

reconsider aa = a, bb = b as Element of [.0,1.] ;

ff . (a,b) = H

hence ff . (a,b) = (a * b) / ((a + b) - (a * b)) by SUBSET_1:def 8, HamIn01; :: thesis: verum